Improved Kinetic Model of Crystallization for Isotactic Polypropylene Induced by Supercritical CO2: Introducing Pressure and Temperature Dependence into the Avrami Equation - Zhang, Ren-Han; Li, Xue-Kun; Cao, Gui-Ping; Shi, Yun-Hai; Liu, Hong-Lai; Yuan, Wei-Kang; Roberts, George W (Industrial & engineering chemistry research, 2011)
Supercritical carbon dioxide (SC-CO2) provides a highly tunable technique to induce changes in morphology and crystallization kinetics of various polymers. In this study, the effect of SC-CO2 treatment on the crystallinity of isotactic polypropylene (i-PP) was analyzed by differential scanning calorimetry (DSC). The Avrami equation is suitable for describing crystallization kinetics of various solids. However, the assumption that the crystallinity approaches 1.0 as the time approaches infinity is not valid for semicrystalline polymers, especially in the atmosphere of SC-CO2. An improved kinetic model for the CO2-induced crystallization of i-PP was purposed by introducing equilibrium crystallinity, as well as temperature- and pressure-dependent terms into the Avrami equation. The parameters of the crystallization kinetics model were obtained by least-squares fitting of the DSC data. The results show that the improved kinetic model provides a reasonable description of the crystallization behavior of i-PP induced by SC-CO2. The successful application of the improved kinetic model to the CO2-induced crystallization of i-PP suggests that this model may be adopted to other SC-CO2-semicrystalline polymer systems.